Chimeric Interaction of Nitrogenase‐Like Reductases with the MoFe Protein of Nitrogenase. (27th February 2020) - Jasper, Jan; Ramos, José V.; Trncik, Christian; Jahn, Dieter; Einsle, Oliver; Layer, Gunhild; Moser, Jürgen
Abstract: The engineering of transgenic organisms with the ability to fix nitrogen is an attractive possibility. However, oxygen sensitivity of nitrogenase, mainly conferred by the reductase component (NifH)2, is an imminent problem. Nitrogenase‐like enzymes involved in coenzyme F430 and chlorophyll biosynthesis utilize the highly homologous reductases (CfbC)2 and (ChlL)2, respectively. Chimeric protein–protein interactions of these reductases with the catalytic component of nitrogenase (MoFe protein) did not support nitrogenase activity. Nucleotide‐dependent association and dissociation of these complexes was investigated, but (CfbC)2 and wild‐type (ChlL)2 showed no modulation of the binding affinity. By contrast, the interaction between the (ChlL)2 mutant Y127S and the MoFe protein was markedly increased in the presence of ATP (or ATP analogues) and reduced in the ADP state. Upon formation of the octameric (ChlL)2 MoFe(ChlL)2 complex, the ATPase activity of this variant is triggered, as seen in the homologous nitrogenase system. Thus, the described reductase(s) might be an attractive tool for further elucidation of the diverse functions of (NifH)2 and the rational design of a more robust reductase. Abstract : In a fix : The catalytic component of nitrogenase (MoFe) forms chimeric complexes with nitrogenase‐like reductases (CfbC)2 and (ChlL)2 . Nucleotide‐dependent protein–protein interactions and the triggering of ATPase activity is investigated. The described reductases and related variants might be an attractive tool to further elucidate the diverse functions of nitrogenase reductase.